Custos de manutenção em HIS construídas com o sistema inovador de parede de placas moldadas in loco: um estudo de casos no conjunto Mariz I em João Pessoa-PB - Silva, Maisa Beatriz Marinho Fausto da (2016)
The buildings are degraded over time, requiring therefore performing maintenance services. These services generate costs, which are the maintenance costs. And when you speak of the study of maintenance costs in Social Housing, this is a little explored subject, and when it comes to the ones which were built with some innovative/ unconventional building system even more. From the knowledge of this gap in terms of maintenance costs on Social Housing and starting from this scenario this dissertation addresses the issue of maintenance costs in Social Housing that used the innovative building system of "sealing walls in molded concrete slabs on site" from the district Mariz I, located in João Pessoa-PB. For the elaboration of the aforementioned dissertation the approach method was deductive, we used the techniques of direct and indirect documentation (extensive) and was adopted probabilistic sampling process. The research that was carried out and has as product this dissertation is classified as to nature, in quantitative, as the purpose in applied, as the type, descriptive and on the design, in survey research. This work proposes to detail all the items that have undergone maintenance over the years studied in the Social Housing addressed, as well as costs arising from this activity, called actual costs; seeking in prior, with the known values of maintenance expenditures, to project itself in terms of future costs for a given period in each case, from the development of a measurement tool for the maintenance costs that uses the principle of cost-significant item (CSI) and aided by statistical mechanisms. However, as the work progressed other relevant factors were becoming notorious, such as the influence of socioeconomic status of the buildings residents with maintenance costs; the calculation of the cost items that were not done maintenance work, but it was found the need to be made, those called potential costs; the perception of the buildings conservation status in the optics of quality of maintenance practice, among others. In general it was found that the maintenance of the activity was carried out informally and in corrective manner. It has been seen that 22% of maintenance items contributed to 95% of the actual costs of the analyzed buildings. The paint item was the most representative, in terms of effective maintenance costs. About the potential costs, in the most of dwellings, there was a tendency of proportional reversal of the amount thereof compared to actual costs. The values of the maintenance costs were directly proportional to the purchasing power of residents, income limitations of these influenced the absence / postponement of the building’s maintenance, and also in the final result of their execution.